The Effect of Cassava Starch and Modified Cassava Starch on Dimension Stability of Alginate Impression - Vinny Puti Belia; Aria Fransiska; Kosno Suprianto (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2024)
Alginate is the most common impression material in dentistry. Alginate is a water-based material and thus has a lack of dimensional stability due to imbibition and syneresis. Dimensional changes in alginate can cause the impression to be less accurate. Dimensional changes can be resolved by modifying alginate, one of which is by adding cassava starch and modified cassava starch. This study aims to determine the effect of adding cassava starch and modified cassava starch on changes in the stability of alginate impression. This research was conducted in an experimental laboratory with a post-test-only control group design and 30 samples. The research was conducted by observing dimensional changes of pure alginate, alginate with 40% cassava starch, and alginate with 40% modified cassava starch at 0 minutes and 30 minutes of impression filling. The smallest dimensional change occurs in alginate with the addition of modified cassava starch 40%; as a result of 0.342% followed by alginate with the addition of natural cassava starch 40%; as a result of 0.592% and pure alginate with the largest dimensional change of as a result 0.85%. The One Way Anova test showed significant differences from the dimensional changes of pure alginate, alginate with 40% cassava starch, and alginate with 40% modified cassava starch. Alginate with the addition of 40% modified cassava starch is more stable than alginate with the addition of 40% cassava starch and pure alginate.